2020
DOI: 10.1039/d0sc01330g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of secondary and tertiary amides without coupling agents from amines and potassium acyltrifluoroborates (KATs)

Abstract: Oxidative amidation of potassium acyltrifluoroborates (KATs) and amines via trifluoroborate iminiums (TIMs) delivers amides without coupling agents. This unusual approach to amides can be applied for the late-stage modification of bioactive molecules and for solid-phase peptide synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
12
0
2
Order By: Relevance
“…Interestingly, a one-pot reaction was later developed by the same group, in which KATs and amines were first reacted to provide TIMs, which were further oxidized with aqueous H 2 O 2 to provide amides ( Scheme 8 , entry 1b). 26 The authors suggested that the reaction proceeded by the addition of peroxide to the TIM and subsequent elimination of the trifluoroborate. This method allowed the synthesis of tertiary amides that would otherwise be inaccessible by the ligation reactions described above and was shown to allow modification of peptides.…”
Section: New Applications Of Acylboranesmentioning
confidence: 99%
“…Interestingly, a one-pot reaction was later developed by the same group, in which KATs and amines were first reacted to provide TIMs, which were further oxidized with aqueous H 2 O 2 to provide amides ( Scheme 8 , entry 1b). 26 The authors suggested that the reaction proceeded by the addition of peroxide to the TIM and subsequent elimination of the trifluoroborate. This method allowed the synthesis of tertiary amides that would otherwise be inaccessible by the ligation reactions described above and was shown to allow modification of peptides.…”
Section: New Applications Of Acylboranesmentioning
confidence: 99%
“…[21] Instead of using hydroxylamines or azides as the amine donor,t he toolbox toward amide formation with acyltrifluoroborates was further expanded to in situ generated chloroamines [22] or oxidation of KAT-iminiums with peroxide (Scheme 4b). [23] Dino Wu TheK AT ligation was furthermore utilized in the formation of PEG-based hydrogels. [24] Encapsulation of bovine chondrocytes through these hydrogels further showcased the biocompatibility of the acyltrifluoroborate group (Scheme 5).…”
Section: Synthetic Applications Of Acylboronate Derivativesmentioning
confidence: 99%
“…N‐protected glycines and a Cbz‐protected l ‐alanine analog were prepared without racemization. These α‐amino acylborons could become building blocks for the synthesis of peptides, as shown by their conversion to the corresponding KATs and preliminary efforts towards oligopeptide synthesis …”
Section: Synthesis From Oxidative Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Das N , N ‐Dimethylamin‐TIM, welches während der Kreuzkupplung mit 1 erhalten wurde, konnte mit einem anderen Amin ausgetauscht werden, um andere tertiäre Amide zu bilden (Schema 3 b). [2, 3, 18] …”
Section: Figureunclassified